Gastrointestinal carcinoma and sarcoma surgery - Koniaris, Leonidas G. (Translational Gastroenterology and Hepatology; Vol 4 (June 2019): Translational Gastroenterology and Hepatology, 2019)
A number of advances in both earlier diagnostic imaging and better treatment options for patients with intra-abdominal malignancies have occurred. Frequently such newer therapies rely on the integration of established surgical and radiation approaches potentially with newer chemotherapies and immunomodulators. Unfortunately, with further study some newer therapies have proven less beneficial than initially suggested. Keeping up with the data supporting newer alternatives, and determining which therapies to provide patients can be a challenge.